Endolysosomal‐Escape Nanovaccines through Adjuvant‐Induced Tumor Antigen Assembly for Enhanced Effector CD8+ T Cell Activation. Issue 15 (1st March 2018) - Qiu, Liping; Valente, Michael; Dolen, Yusuf; Jäger, Eliezer; Beest, Martin ter; Zheng, Liyan; Figdor, Carl G.; Verdoes, Martijn
Abstract: The activation of tumor‐specific effector immune cells is key for successful immunotherapy and vaccination is a powerful strategy to induce such adaptive immune responses. However, the generation of effective anticancer vaccines is challenging. To overcome these challenges, a novel straight‐forward strategy of adjuvant‐induced tumor antigen assembly to generate nanovaccines with superior antigen/adjuvant loading efficiency is developed. To protect nanovaccines in circulation and to introduce additional functionalities, a biocompatible polyphenol coating is installed. The resulting functionalizable nanovaccines are equipped with a pH (low) insertion peptide (pHLIP) to facilitate endolysosomal escape and to promote cytoplasmic localization, with the aim to enhance cross‐presentation of the antigen by dendritic cells to effectively activate CD8 + T cell. The results demonstrate that pHLIP‐functionalized model nanovaccine can induce endolysosomal escape and enhance CD8 + T cell activation both in vitro and in vivo. Furthermore, based on the adjuvant‐induced antigen assembly, nanovaccines of the clinically relevant tumor‐associated antigen NY‐ESO‐1 are generated and show excellent capacity to elicit NY‐ESO‐1‐specific CD8 + T cell activation, demonstrating a high potential of this functionalizable nanovaccine formulation strategy for clinical applications. Abstract : Cancer vaccination is a powerful strategy to induce the activation of tumor‐specific effector CD8 + T cells, which is key for successful immunotherapy . Here, novel nanovaccines are developed with convenient operation, superior antigen/adjuvant loading efficiency, and endolysosomal‐escape capability to efficiently enhance CD8 + T cell activation. The potential of these nanovaccines in clinical application is also well proved.